PENGARUH MODAL KERJA DAN PENJUALAN TERHADAP LABA BERSIH PADA PERUSAHAAN PERKEBUNAN SAWIT YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2023 - Ahmad Yusuf Aras; Ery Bestary Al Haitamy; Pramesti Nurul Adinda (LP2M Politeknik Jambi, 2025)
The role of working capital and sales is very influential on the survival of the company in its operation. The use of these two factors will give an idea that the effectiveness of the use of working capital and sales will be directed at increasing and decreasing the company's net profit. The purpose of this study is to prove the influence of working capital and sales on net profit in oil palm plantation companies. This study takes data in a time series in the form of financial statements for the period 2019-2023. The analysis tool used is the spss version 25 program with the data analysis used in this study, namely the classical assumption test and multiple linear regression test and the R2 determination coefficient test and hypothesis testing using partial tests (t) and simultaneous tests (F) with the intention of determining the influence of independent variabels on bound variabels at a confidence level of 63.2% (á = 0.05). The results of this study are based on (Test-t), working capital has no effect on net profit partially with a calculated value of 1.374 < ttable 2.011, while sales have an effect on net profit partially with a calculated value of 6.101 > ttable 2.011. Simultaneous (Test-F), working capital and sales immediately affected the net profit with the value of Fcal > Ftable, which was 40.330 > 3.20.